2012
DOI: 10.2105/ajph.2011.300613
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Unexpected Infant Deaths: Sleep Environment and Circumstances

Abstract: We identified modifiable sleep environment risk factors in a large proportion of the SUIDs assessed in this study. Our results make an important contribution to the mounting evidence that sleep environment hazards contribute to SUIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 24 publications
2
42
1
Order By: Relevance
“…Locally, a systematic approach to inquiry can lead to better understanding of how and why a child died-eg, more rigorous approaches to investigation have been linked to the identification of infections, congenital malformations, intentional and unintentional injuries, and metabolic disorders as causes of sudden unexpected deaths in infants. (70)(71)(72)(73) A diagnosis is invaluable to a bereaved parent and might allow them to undergo counselling for future pregnancies. However, at a state and national level, child death review teams need to show an increased ability to move from case review to effective action.…”
Section: Future Challengesmentioning
confidence: 99%
“…Locally, a systematic approach to inquiry can lead to better understanding of how and why a child died-eg, more rigorous approaches to investigation have been linked to the identification of infections, congenital malformations, intentional and unintentional injuries, and metabolic disorders as causes of sudden unexpected deaths in infants. (70)(71)(72)(73) A diagnosis is invaluable to a bereaved parent and might allow them to undergo counselling for future pregnancies. However, at a state and national level, child death review teams need to show an increased ability to move from case review to effective action.…”
Section: Future Challengesmentioning
confidence: 99%
“…Multiple imputation has been previously used for analyses of the CDR-CRS database. 20,23 Multiple imputation predicts values for incomplete variables by using regression equations from complete variables. This minimizes assumptions that the subset of cases with complete data are representative of the entire sample population.…”
Section: Discussionmentioning
confidence: 99%
“…The CDR-CRS, funded by the Maternal and Child Health Bureau, is a web-based system used for the collection, reporting, and analysis of individual child deaths by state child death review teams. 19,20 The database includes .84 100 child deaths, including .45 300 infant deaths. 19 As of June 2014, 35 states were contributing to the database, which contains .1700 data elements, with each element linked to definitions and a code book to ensure standardization and consistency in reporting.…”
Section: Data Sourcementioning
confidence: 99%
“…Additionally, a study by Schnitzer, Covington & Dykstra (2012) found 70% of SUIDS were associated with infants sleeping on a surface not intended for infant sleep. Of these, 64% of SUIDS infants were sharing the sleep surface with a person or animal and almost half were sharing the sleep surface with an adult.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of these, 64% of SUIDS infants were sharing the sleep surface with a person or animal and almost half were sharing the sleep surface with an adult. (Covington & Dykstra, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%